Infektif Endokarditis Pada Penyakit Jantung Tiroid - Pradita Diah Permatasari (Fakultas Kedokteran, Universitas Andalas, 2020)
Infective endocarditis is an endocardial surface infection of the heart including heart valves that can be fatal. Occurs because there is damage to the surface of the endocardium and the entry of bacteria into the circulation. The presence of cardiac lesions such as mitral regurgitation can be a predisposing factor for infective endocarditis. Patients were diagnosed with infective endocarditis based on a scoring system consisting of clinical symptoms, imaging, and blood culture findings, namely: modified Duke criteria. Treatment of infective endocarditis consists of giving antibiotics and evacuating vegetation by surgery. Surgical action is indicated if there is symptoms of heart failure, uncontrolled infections and vegetation size are too large, causing the risk of embolism.